ANALISIS PENERAPAN KEBIJAKAN PERATURAN MENTERI PERHUBUNGAN NO 82 TAHUN 2018 TENTANG ALAT PENGENDALI DAN PENGAMAN PUNGGUNA JALAN DI KECAMATAN LIMBOTO KABUPATEN GORONTALO - Sakbir (STISIPOL Mujahidin Buol, 2023)
This study aims to determine the implementation of the Regulation of the Minister of Transportation of the Republic of Indonesia No. 82 of 2018 concerning Road User Control and Safety Devices in Limboto District, Gorontalo Regency. The research method uses a qualitative type. The results of the study indicate that the implementation of the Regulation of the Minister of Transportation of the Republic of Indonesia No. 82 of 2018 concerning the manufacture of road controllers is not optimal. This can be seen from the absence of socialization carried out by the Department of Transportation to government officials and the people of Limboto District about the standard for using speed bumps so that both the apparatus and the public do not know about it. In addition, the attitude of policy implementing officers lacks supervision and coordination on the implementation of the policy of the Minister of Transportation of the Republic of Indonesia No. 82 of 2018 concerning the manufacture of road controllers and seems to have neglected the construction of road controllers that are not in accordance with existing standards.